Isolation and Identification of Bacteria in Post-Operated Wound Patients at Sabratha Teaching Hospital in Libya - alashoury, halima; Khalid Othman, (AlQalam Journal of Medical and Applied Sciences, 2026)
Hospital‑acquired infections (HAIs) remain a serious global health concern, with wound infections representing the most common nosocomial infection, particularly among surgical patients. Surgical site infections are the second most frequent type of HAI, accounting for approximately 24% of all hospital‑acquired infections. In this study, samples from post‑operative wounds were collected and inoculated onto blood agar and MacConkey’s agar under aseptic conditions. Plates were incubated at 37°C for 18–24 hours. All cultures were examined macroscopically for growth, colonial morphology, and changes in the media. Plates showing visible growth were subjected to standard bacteriological tests, including catalase, coagulase, oxidase, urease, and citrate utilization. Plates without visible growth were re‑incubated and examined daily for up to seven days. Colonies were identified by Gram staining and conventional bacteriological methods for Gram‑positive and Gram‑negative organisms. A total of 22 patients were included between May and June 2023. Of these, 20 had undergone surgical procedures, while 2 were outpatients. The study population comprised 7 males (31.8%) and 15 females (68.1%). The most predominant bacterial isolate was Staphylococcus spp. (10 isolates, 62.5%), followed by Pseudomonas spp. (4 isolates, 25%) and Klebsiella spp. (2 isolates, 12.5%). Six samples showed no bacterial growth. The overall rate of wound infection was high among the patients studied, with Staphylococcus spp. representing the most frequent Gram‑positive isolate and Pseudomonas spp. the most frequent Gram‑negative isolate. The rate of wound was high among our patients, Staphylococcus spp was the highest gram positive isolate while Pseudomonas spp was the highest among gram negative. Key words: post-operated wound infection, Bacteria, Patients, Predominant, Libya, Staphylococcus.